Exposure of Human Prostaspheres to Bisphenol A Epigenetically Regulates SNORD Family Noncoding RNAs via Histone Modification - Ho, Shuk-Mei (Endocrinology, 2015)
Bisphenol A (BPA) is a ubiquitous endocrine disruptor exerting lifelong effects on gene expression in rodent prostate cancer (PCa) models. Here, we aimed to determine whether epigenetic events mediating the action of BPA on human prostaspheres enriched in epithelial stem-like/progenitor cells is linked to PCa. We performed genome-wide transcriptome and methylome analyses to identify changes in prostaspheres treated with BPA (10nM, 200nM, and 1000nM) or estradiol-17β (E2) (0.1nM) for 7 days and validated changes in expression, methylation, and histone marks in parallel-treated prostaspheres. BPA/E2-treatment altered expression of 91 genes but not the methylation status of 485 000 CpG sites in BPA/E2-treated prostaspheres. A panel of 26 genes was found repressed in all treatment groups. Fifteen of them were small nucleolar RNAs with C/D motif (SNORDs), which are noncoding, small nucleolar RNAs known to regulate ribosomal RNA assembly and function. Ten of the most down-regulated SNORDs were further studied. All 10 were confirmed repressed by BPA, but only 3 ratified as E2-repressed. SNORD suppression showed no correlation with methylation status changes in CpG sites in gene regulatory regions. Instead, BPA-induced gene silencing was found to associate with altered recruitments of H3K9me3, H3K4me3, and H3K27me3 to 5′-regulatory/exonic sequences of 5 SNORDs. Expression of 4 out of these 5 SNORDs (SNORD59A, SNORD82, SNORD116, and SNORD117) was shown to be reduced in PCa compared with adjacent normal tissue. This study reveals a novel and unique action of BPA in disrupting expression of PCa-associated SNORDs and a putative mechanism for reprogramming the prostasphere epigenome via histone modification.